Promoting micro-irrigation technologies that reduce poverty - International Water Management Institute (International Water Management Institute, 2006)
According to research done by the International Water Management Institute (IWMI), one-third of the world?s population will face absolute water scarcity by the year 2025. Among the worst hit will be regions in Asia, the Middle-East and Sub-Saharan Africa, home to some of the largest concentrations of rural poverty in the world. Policymakers, researchers, NGOs, and farmers are pursuing various technical, institutional and policy interventions to meet this challenge. Micro-irrigation technologies, commonly in use in water scarce areas of developed countries, constitute one such intervention with the ability to use water more efficiently in irrigated agriculture. These technologies can improve productivity; raise incomes through crop yields and outputs; and enhance food security of households. Numerous studies have established the gains from micro-irrigation adoption and several government and non-government organizations are engaged in actively promoting the technologies. In India, micro-irrigation technologies have been marketed for more than three decades. The main vehicle of government policies to promote micro-irrigation systems are product subsidies?in certain cases up to 90 percent. However, there has been a lukewarm response to such initiatives from farmers, especially smallholders. This can be attributed to several causes: lack of access to groundwater, lack of cash, crop specificity of the available micro-irrigation technologies, lack of know-how, poor product quality and absence of adequate credit facilities (Narayanamoorthy 1996). Studies show that despite active promotion, the appeal of these technologies has remained confined to ?gentlemen farmers??wealthier farmers who produce commercial crops (Shah and Keller 2002). Despite these constraints, in certain pockets of India, these technologies have become a popular choice among farmers. It is notable that, in some of these cases, the technologies have been adopted in the absence of government subsidies. However, IWMI?s work shows that in general special efforts are required to market cost appropriate technologies to the poor and smallholder farmers. Drip irrigation is often promoted for reasons that do not match with the farmers? main concerns. While the government promotes drips as longterm investments for water saving and sustainable agriculture, the farmers look for more immediate and assured benefits, such as lower costs and increased incomes.